Planning of collision-free trajectory for mobile manipulators - Pająk, Grzegorz (Zielona Góra: Uniwersytet Zielonogórski)
A method of planning sub-optimal trajectory for a mobile manipulator working in the environment including obstacles is presented. The path of the end-effector is defined as a curve that can be parameterized by any scaling parameter, the reference trajectory of a mobile platform is not needed. Constraints connected with the existence of mechanical limits for a given manipulator configuration, collision avoidance conditions and control constraints are considered.
Keywords: mobile manipulator; path following; trajectory planning; penalty function; control constraints